Case manipulation of football match score by the referee in the framework of fulfilling sports purposes - Emmilia Rusdiana,; Pudji Astuti,; Gelar Ali Ahmad,; Vita Mahardhika,; Nurul Hikmah, (Technium Social Sciences Journal, 2023)
The manipulation of football match scores in Indonesia is familiar and continues to increase. The settlement of the case in the judge's decision was based on two criminal acts, namely the crime of fraud (Article 378 of the Criminal Code) and bribery (UU No. 11 of 1980). It is stated in several judge's decisions, including in Judge's Decision No.31/Pid.Sus/2020/PN.Smd and Judge's Decision No.48/Pid.Sus/2019/PN BNR. Manipulation of match scores as an attempt to violate the goals of the sport of football. This research aims to verify cases of match score manipulation by referees in realizing sports goals. The results of the discussion prove that the two judges' decisions that classify match score manipulation In the two judges' decisions that classify match score manipulation cases as fraud and bribery, there is the fulfillment of the elements in both of these crimes. In contrast, the subject of the violation is the referee who leads the match, which requires Integrity and leadership character. Then the goal of a soccer match is to support the embodiment of the formation of national values and character. Then when a referee is involved in a match score manipulation case, it means he has generally failed the goals of the sport.